The The Effect of ESA and PPP Method on Students’ Speaking Skill - Hulwana, Halad (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
The problem was found class that students got some difficulties in speaking skill. ESA (Engage, Study, and Activate) and PPP (Participation, Practice, and Production) techniques are teaching methods to teach English as a Foreign Language. It is believed that these methods are suitable to teach speaking because by using this method the student will have better participation in the classroom, encourage their curiosity in English learning. The aims of research was to analtyze speaking performance between the students who learned using ESA,and PPP. A quasi experimental research was administered as the design of the research. The sample was taken by using purposive sampling technique. The data was collected by using a speaking test. The data was analysed using the SPSS Independent T-test. Based on the result of independent sample t-test, it was found that ESA class had the significance value (Sig.) was 0.589 which was higher than the value 0.05. Thus, H0 was accepted, which meant that speaking skills of students who were taught by using ESA were the same as speaking skills of students who were taught by using conventional method. While PPP class had significance value (Sig.) was 0.029 which was smaller than the value 0.05 which indicated that speaking skills of students who were taught by using PPP were not the same as speaking skills of students who were taught by using conventional. Therefore, using PPP technique has positive effect for the students in speaking skill rather than ESA and Conventional.